DC jazz : stories of jazz music in Washington, DC - Jackson, Maurice, 1950-; Ruble, Blair A., 1949- (Georgetown University Press, 2018)
The conventional history of jazz music in the United States begins in New Orleans, moves upstream along the Mississippi River to Chicago, then by rail into New York before exploding across the globe. But in fact the nation's capital has been a fertile city for jazz for a century. Some of the most important clubs in the jazz world have opened and closed their doors in Washington, DC; some of its greatest players and promoters were born there and continue to reside in the area; and some of the local institutions so critical to supporting this uniquely American form of music--including Congress and the Smithsonian Institution and the Library of Congress and the Historical Society of Washington, DC--remain vigorous advocates. Edited by noted historians Maurice Jackson and Blair Ruble, this book is a collection of original and fascinating stories about the DC jazz scene, from the cultural hotbed of Seventh and U Streets to the role of jazz in desegregating the city to the great Edward "Duke" Ellington to women in jazz to seminal contributions of the University of District of Columbia and Howard University. The book also includes three poems by Washington, DC poet E. Ethelbert Miller. A copublishing initiative with the Historical Society of Washington, DC, the book includes over thirty museum-quality photographs and a guide to resources for learning more about Washington, DC jazz